2019
DOI: 10.1590/1980-265x-tce-2017-0187
|View full text |Cite
|
Sign up to set email alerts
|

Use of Computational Tools as Support to the Cross-Mapping Method Between Clinical Terminologies

Abstract: Objective: to reflect on the use of computational tools in the cross-mapping method between clinical terminologies. Method: reflection study. Results: the cross-mapping method consists of obtaining a list of terms through extraction and normalization; the connection between the terms of the list and those of the reference base, by means of predefined rules; and grouping of the terms into categories: exact or partial combination or, in more detail, similar term, more comprehensive term, more restricted term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In terms of form, the document indicates the need of formal computational representation, so that the mapping is computer readable and allows computational processing and machine translation (2) . In addition to facilitating the cross-terminology mapping process, computational representation reduce manual mapping errors and the time spent by researchers (18) .…”
Section: Iso/tr 12300:2016 Technical Documentmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of form, the document indicates the need of formal computational representation, so that the mapping is computer readable and allows computational processing and machine translation (2) . In addition to facilitating the cross-terminology mapping process, computational representation reduce manual mapping errors and the time spent by researchers (18) .…”
Section: Iso/tr 12300:2016 Technical Documentmentioning
confidence: 99%
“…The complexity of the cross-terminology mapping process requires attention, ability and time. To optimize the resources involved, health informatics can support this process (18) through self-organizing mapping (2) , so named when computational tools are used. This enables matching terms through established rules (2) , providing direct identification of the possible candidate term or terms to be evaluated and validated by the researcher (2,26) .…”
mentioning
confidence: 99%
“…The purpose of the application of a standardized terminology is to direct the work method, which influences the documentation of practices, guidance and support for clinical reasoning and the naming of the phenomena of the profession, thus contributing to the framework of specific knowledge 7 . In this context, The language of diagnoses statements, results and nursing interventions can be guided by terminologies, and the most used in the Brazilian scenario are the International Classification for Nursing Practice (CIPE®), the NANDA-International (NANDA-I), the Nursing Interventions Classification (NIC) and Nursing Outcomes Classification (NOC) [8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…With regard to automating mappings between ICNP terms and other terminologies, precoordinated terms should be considered in the UMLS in English [ 24 ]. Further, because the primitive terms of the ICNP are arranged in a 7-axis model, natural language processing (NLP) algorithms and techniques can support its mapping [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the hypothesis of the study that is reported in this paper is as follows: mapping automation, through computational algorithms, collaborates with the manual mapping process. The goal of this study is to compare results of manual and automated term mapping processes to verify if the automated method is adequate to support the task of mapping, considering the challenges of the manual cross-term mapping process [ 25 ], the possible contribution of automated mapping to nursing terminologies [ 11 , 13 , 14 ], and the incipience of studies that compare manual and automated mappings.…”
Section: Introductionmentioning
confidence: 99%